2021
DOI: 10.3389/fphar.2021.697912
|View full text |Cite
|
Sign up to set email alerts
|

β2-and β3-Adrenergic Receptors Contribute to Cancer-Evoked Pain in a Mouse Model of Osteosarcoma via Modulation of Neural Macrophages

Abstract: The mechanisms involved in the development and maintenance of cancer pain remain largely unidentified. Recently, it has been reported that β-adrenergic receptors (β-ARs), mainly β2-and β3-ARs, contribute to tumor proliferation and progression and may favor cancer-associated pain and neuroinflammation. However, the mechanism underlying β-ARs in cancer pain is still unknown. Here, we investigated the role of β1-, β2-and β3-ARs in a mouse model of cancer pain generated by the para-tibial injection of K7M2 osteosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 50 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Additionally, a cisplatin-induced neuropathy model affected catalase levels protected by co-administration of melatonin, revealing its potent antioxidant activity [ 144 ]. Recently, the role of propranolol in tumor suppression oxidative stress in neural macrophages has been reported by targeting β adrenergic receptors [ 145 ]. Its neuroprotective effect in several models of transient focal stroke was attributed to its antioxidant and free radical scavenger properties [ 146 , 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a cisplatin-induced neuropathy model affected catalase levels protected by co-administration of melatonin, revealing its potent antioxidant activity [ 144 ]. Recently, the role of propranolol in tumor suppression oxidative stress in neural macrophages has been reported by targeting β adrenergic receptors [ 145 ]. Its neuroprotective effect in several models of transient focal stroke was attributed to its antioxidant and free radical scavenger properties [ 146 , 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature data reported the β3-ARs' ability to reduce tumor growth and metastases. Bruno et al showed that β-ARs, principally through β2and β3-ARs, supported tumor growth and cancer pain in a murine model of syngeneic osteosarcoma (OS) [184].…”
Section: β3-ar In Pathologymentioning
confidence: 99%
“…Zheng et al showed that β3-AR expression was significantly increased in NB tissues and that β3-AR-pathway blockade inhibited cell growth via mTOR signaling suppression that enlightened a novel regulatory axis of β3-AR and mTOR in NB cells [260]. Moreover, data have shown the pro-tumoral role of β3-AR in NB and its involvement in tumor growth in a syngeneic murine model [184]. In the murine Neuro2A cell line, both the antagonism of β3-AR and β3-AR silencing inhibited cell growth and progression, in particular, the antagonism reduced the stemness markers' expression but enhanced the markers of differentiation [258].…”
Section: β3-ar In Neuroblastomamentioning
confidence: 99%
“…Recent findings from Bruno et al have revealed that β2-and β3-adrenergic receptor (AR)-expressed neural macrophages contribute to cancer-evoked pain through utilizing the K7M2 osteosarcoma-bearing mouse model. 53 In their study, the progression of mechanical allodynia elicited by oxidative stress is closely associated with the recruitment of neural macrophages. Importantly, the antagonism of β2-and β3-ARs is found to not only result in the supression of tumor growth, but also in cancer pain, together highlighting the therapeutic potential of the β2-and β3-ARs signaling against osteosarcoma-evoked pain.…”
Section: The Involvement Of Immune Cells In Cancer-related Neuropathi...mentioning
confidence: 99%
“…Importantly, the antagonism of β2-and β3-ARs is found to not only result in the supression of tumor growth, but also in cancer pain, together highlighting the therapeutic potential of the β2-and β3-ARs signaling against osteosarcoma-evoked pain. 53 Through using human monocyte-derived macrophages, Fei et al have demonstrated that α7 nicotinic acetylcholine receptor (α7nAChR) in tumor-associated macrophages suppresses colorectal cancer (CRC) metastasis and relavant pain signaling. 47 When co-culturing with LoVo cells, a commonly-used CRC cell line, the knockdown of α7nAChR in macrophages dramatically attenuated the phosphorylation of STAT3, p85 as well as p65.…”
Section: The Involvement Of Immune Cells In Cancer-related Neuropathi...mentioning
confidence: 99%